Economic consequences of the 1933 Soviet famine - Natalya Naumenko (European Historical Economics Society (EHES), 2024)
Using recently discovered archival data, this article studies the changes in the Soviet population and the urbanization patterns after the 1933 famine. It documents that, although most of the direct victims lived in the rural areas, the famine is associated with a persistent negative change in the urban population. In fact, the rural population gradually recovered while urban settlements in more affected areas became permanently smaller. The paper shows that these changes were not planned in the First Five-Year Plan (1928-1933), but that subsequent plans may have incorporated and exacerbated the differences in urbanization that occurred during the years of rural crisis. The paper argues that the shortage of labor during the crucial years of the rapid industrialization hindered the development of cities in areas stricken by the famine. Thus, the timing of the shock to population appears to be important. While established urban networks tend to recover from large temporary negative shocks, the lack of people during construction and rapid growth might have a permanent negative impact.
Keywords: N34; O18; P25; R12; R13; 330; Russia; Famine consequences; Multiple equilibria